2018
DOI: 10.1161/circoutcomes.117.004482
|View full text |Cite
|
Sign up to set email alerts
|

Health Economic Analysis of Access Site Practice in England During Changes in Practice

Abstract: The transition to TRA in England has been associated with significant cost savings across the national healthcare system, in addition to the well-established clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 22 publications
2
37
0
Order By: Relevance
“…The transradial approach (TRA) has been widely adopted for coronary, peripheral, and cerebrovascular endovascular procedures due to the overwhelming evidence demonstrating a reduction in access site complications, in addition to improved patient preference and cost compared with traditional transfemoral access (TFA) 1–9. Led by the interventional cardiology community, large randomized multicenter trials such as the Radial versus Femoral Access for Coronary Angiography and Intervention in Patients with Acute Coronary Syndrome (RIVAL) and Minimizing Adverse Haemorrhagic Events by Transradial Access Site and the Systemic Implementation of AngioX (MATRIX) studies, with over 7000 patients each, have reported a greater than 60% reduction in vascular complications as well as significant decreases in all-cause mortality and net adverse clinical events with TRA 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…The transradial approach (TRA) has been widely adopted for coronary, peripheral, and cerebrovascular endovascular procedures due to the overwhelming evidence demonstrating a reduction in access site complications, in addition to improved patient preference and cost compared with traditional transfemoral access (TFA) 1–9. Led by the interventional cardiology community, large randomized multicenter trials such as the Radial versus Femoral Access for Coronary Angiography and Intervention in Patients with Acute Coronary Syndrome (RIVAL) and Minimizing Adverse Haemorrhagic Events by Transradial Access Site and the Systemic Implementation of AngioX (MATRIX) studies, with over 7000 patients each, have reported a greater than 60% reduction in vascular complications as well as significant decreases in all-cause mortality and net adverse clinical events with TRA 10 11.…”
Section: Introductionmentioning
confidence: 99%
“…The radial artery approach has become an increasingly popular alternative for arterial access in endovascular interventions 1. First described by Campeau2 nearly three decades ago, the use of a percutaneous radial artery approach for angiography has seen a significant increase in the field of interventional cardiology owing to comparative data demonstrating superiority in clinical outcome, patient satisfaction, and cost reduction compared with the standard femoral artery access 2–11. The association between radial access and reduced post-procedural bleeding, major vascular complications, overall adverse clinical events, and hospital length of stay is well documented in the cardiology literature 12–15.…”
Section: Introductionmentioning
confidence: 99%
“…Radial access for coronary and peripheral interventional angiography has dramatically increased worldwide since its introduction in 1989 by Campeau. Interventional cardiology studies comparing a transradial approach (TRA) with a transfemoral approach (TFA) have shown an unequivocal benefit of the former, with reduced morbidity and mortality, greater patient preference, and cost reductions [14]. Performing the endovascular interventions via forearm radial artery (FRA) is considered preferable due to the lower risk of access site bleeding his is caused by anatomical proximity of the radial artery to the "bone basement" [15].…”
Section: Discussionmentioning
confidence: 99%